Use of Russia's Information and Communication Technologies in Political Instrumentalization of Ukraine's History - Danylenko, Serhiy; Shcherbatiuk, Olena (Wydawnictwo Naukowe Wydziału Nauk Politycznych i Dziennikarstwa UAM, 2021)
The political instrumentalization of the history of Ukraine carried out by the Russian Federation in the framework of the information war against Ukraine is covered in this article. This instrumentalization is exercised through media communication employing historical and political myths and narratives to vindicate Russia’s aggressive actions. The latest information and communication technologies used by the Kremlin in the information war against Ukraine have been identified in this paper. Such destructive efforts often derail Ukrainian-Polish relations, which are particularly sensitive to historical and political issues. The reasons for the drawbacks of the Ukrainian authorities in counteracting the information aggression on the part of the Russian Federation are distinguished, and the measures that would contribute to an effective response to such aggression are outlined.

W artykule omówiono polityczną instrumentalizację dziejów Ukrainy prowadzoną przez Federację Rosyjską w ramach wojny informacyjnej z Ukrainą. Ta instrumentalizacja jest realizowana poprzez komunikację medialną, wykorzystującą mity i narracje historyczne i polityczne, aby usprawiedliwić agresywne działania Rosji. W artykule zidentyfikowano najnowsze technologie informacyjno-komunikacyjne wykorzystywane przez Kreml w wojnie informacyjnej z Ukrainą. Takie destrukcyjne wysiłki często negatywnie wpływają na stosunki ukraińsko-polskie, które są szczególnie wrażliwe na kwestie historyczne i polityczne.
Wykorzystanie rosyjskich technologii informacyjno-komunikacyjnych w instrumentalizacji politycznej historii Ukrainy
Keywords: disinformation; Russia's information war against Ukraine; political instrumentalization of history; media; dezinformacja; wojna informacyjna Rosji z Ukrainą; polityczna instrumentalizacja historii; media